PENERAPAN ACCESS CONTROL SEBAGAI SALAH SATU STRATEGI PENCEGAHAN KEJAHATAN SITUASIONAL DI LADANG MINYAK DURI - Muhammad Fauzan (Jurnal Kriminologi Indonesia, 2011)
The objective of this research is to make an overview of the application of situational crime prevention strategies, focus in the application of access control, in Duri Field by PT. Chevron Pacific Indonesia. The research used qualitative method, so that the data obtained through the interview and direct observation to the location. The result of this research is the fact of the application of crime prevention strategies in the Duri Field that are not only confined by the physical aspects, but there are also the social and psychological aspects. The physical aspect of the access control concept would not be effective if the social and psychological aspects do not support them.